Penggunaan Tayamum Untuk Melaksanakan Shalat Fardhu Di Tempat Pemberhentian Bus Dalam Perjalanan Lampung Ke Medan NURUT HUKUM ISLAM - Adrianto (Institut Syekh Abdul Halim Hasan Binjai, 2024)
on the way Lampung to Medan at the bus stop found a small room the less clean water is used for thaharah and meanwhile prayer time has entered On the other hand, passengers have a problem with good dust which can be used for tayamum. To answer this problem the author uses an approach ushuli namely analyzing the main points of the problem with approach dalil, namely using dalil al quran and dalil hadist and related to the opinions of para cleric fiqh relating to undiscovered water and dust in the sense of looking for soil good thing to do tayamum. Research result, The use of tayammum by seeing because it's allowed tayamum that is, it is prayer time and no water was found. The traveler did it tayamum for prayer fardhu is allowed, if he doesn't find water. If the traveler finds water then the traveler performs ablution. and holy dust is dust that exists on the ground surface like on the ground around the ground like grass, trees and so forth.